(untitled) (Лучшие интеллектуальные исследования, 2025)
Аннотация. В данной статье рассматривается важное искусство культурного перевода, которое помогает сохранить подтекст и особенности родного языка в процессе перевода, а также проблемы, с которыми сталкиваются переводчики: как передать культурные нюансы, идиомы и образы из одного языка в другой с учетом контекста. В статье будут представлены методы, подходы и инструменты, которые помогают переводчикам достичь максимальной точности в передаче смысла оригинального текста без потери его культурной ценности. Abstract. This article discusses the important art of cultural translation, which helps preserve the subtext and features of the native language during the translation process, as well as the challenges that translators face: how to convey cultural nuances, idioms and images from one language to another, taking into account the context. The article will present methods, approaches and tools that help translators achieve maximum accuracy in conveying the meaning of the original text without losing its cultural value.